Fraud, convenience, and e-voting: how voting experience shapes opinions about voting technology. Issue 2 (3rd April 2018) - Alvarez, R. Michael; Levin, Ines; Li, Yimeng
ABSTRACT: In this article, we study previous experiences with voting technologies, support for e-voting, and perceptions of voter fraud, using data from the 2015 Cooperative Congressional Election Study. We find that voters prefer systems they have used in the past, and that priming voters with voting fraud considerations causes them to support lower-tech alternatives to touch-screen voting machines — particularly among voters with previous experience using e-voting technologies to cast their votes. Our results suggest that as policy makers consider the adoption of new voting systems in their states and counties, they would be well-served to pay close attention to how the case for new voting technology is framed.